Efektivitas sistem gabungan penukar kalor-udara tanah dengan kolektor surya untuk pendinginan ruangan di kota Medan - Tulus Burhanuddin Sitorus; Syahrul Abda (Jurnal Teknosains, 2022)
Energy is one of the main things in a country's economic growth, but saving energy is one of the main challenges in the world today. In developing countries such as Indonesia, the energy sector is considered a crucial sector, because consumption demand increases compared to production. Therefore, to reduce energy consumption it is necessary to save energy. Earth-air heat exchanger cooling systems are one of them. The research objective was to determine the effectiveness performance of the EAHE system on changes in room temperature according to weather conditions in Medan city. The implication of this research is to reduce the consumption of electricity or fuel oil and environmental pollution. The test room has dimensions of 200 cm x 200 cm x 200 cm. Testing using a flat plate type solar collector to help the process of air movement by taking advantage of differences in air temperature. The testing process starts at 08.00 WIB to 17.00 WIB for nine hours everyday. The measurement results show that various weather conditions include radiation intensity, ambient temperature and humidity. During the test, the radiation intensity ranged from 38.10-892.12 W/m2, the variation in ambient temperature from 24.65-35.29oC and the average air humidity 68.93%. The experimental data showed that the fluctuation of indoor air temperature ranged from 23.01 to 31.84oC and the average room temperature 27.83oC. This study resulted in an average effectiveness value of the EAHE system of 51.49%. According to the result of the statistical studies, the weather conditionsthe effectiveness of the EAHE system by51,56%.